Functional and Olfactory Outcomes of Inferior Turbinate Hypertrophy Reduction with Laser, Radiofrequency, and Bipolar - Mustafa Caner Kesimli; Eren Yılmaz; Aytuğ Altundağ (The Turkish Journal of Ear Nose and Throat)
Objective: This study aims to compare the effects of bipolar cauterization, radiofrequency ablation, and laser reduction methods, which are frequently used for turbinate reduction, on recovery times and olfactory functions in the early postoperative period.Materials and Methods: The olfactory functions of all patients were preoperatively evaluated with the Sniffin’ Sticks test. To assess the effects on olfactory functions, olfactory tests were repeated in the third month after the operation. The patients were examined weekly, and the resolving time of the crusts was recorded.Results: The endoscopic turbinate reduction was performed with bipolar cautery in 50 patients, with radiofrequency ablation in 50 patients, and with laser ablation in 50 patients. There was no statistically significant difference between the techniques used regarding the severity of the olfactory function loss in the third month (p=0.546). It was observed that the resolving time of the crusts was the shortest in the group treated with the Holmium-YAG laser and the longest in the patients who underwent bipolar cautery (p<0.001). Parosmia persisted in only 9 patients in the postoperative third month (BP:7, RF:2, L:0) (p=0.049). In addition, it was determined that nasal dryness and pain (as assessed by visual analog score) were the most in the bipolar group (p=0.001 and p=0.005, respectively), and there was no significant difference between the laser and radiofrequency groups in terms of these symptoms (p=0.53 and P=0.96, respectively).Conclusion: Patients who underwent Holmium laser turbinate ablation had less crusting and less olfactory function loss in the early period compared to those who underwent radiofrequency and bipolar turbinate reduction.